2013
DOI: 10.1097/fbp.0b013e32835d5278
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive conditioning with the nicotine stimulus

Abstract: Interoceptive conditioning involving the nicotine stimulus likely contributes to chronic tobacco use. To better understand the nature of this interoceptive conditioning, we compared generalization during repeated extinction with generalization in a 'transfer of extinction' test using a wide range of test doses. Rats were first trained in the discriminated goal-tracking task in which nicotine (0.2 or 0.4 mg/kg), but not saline, was paired with repeated intermittent access to sucrose. Across sessions, nicotine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…All injections were subcutaneous (SC) in a volume of 1 ml/kg. Previous research suggests the doses utilized in this study and reported below produce robust discrimination and optimal transfer of extinction back to nicotine (Besheer et al , 2004; Polewan et al , 2013; Reichel et al , 2010). …”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…All injections were subcutaneous (SC) in a volume of 1 ml/kg. Previous research suggests the doses utilized in this study and reported below produce robust discrimination and optimal transfer of extinction back to nicotine (Besheer et al , 2004; Polewan et al , 2013; Reichel et al , 2010). …”
Section: Methodsmentioning
confidence: 80%
“…One such factor, and our focus in this report, is learning which involves the interoceptive nicotine stimulus and its contribution to the tenacity of the smoking habit and nicotine dependence (Besheer et al , 2004; Bevins et al , 2012; Bevins and Murray, 2011; Charntikov et al , 2014; Glautier et al , 1996; Polewan et al , 2013; Troisi, 2006). To determine the role of learned associations with the nicotine stimulus, our lab utilizes a discriminated goal-tracking task (Besheer et al , 2004; Charntikov et al , 2014; Pittenger and Bevins, 2013a; Polewan et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations